Rousseau Today
IX, 270 p. 5 illus.
Keywords: “This highly innovative and wide-ranging collection 'reloads' Rousseau as a resource for current social and political theory, covering both well-known topics and less familiar ones.” —William Outhwaite, Professor Emeritus of Sociology, University of Newcastle, UK “This scintillating volume on Rousseau—with its internationally divergent and original chapters—confronts the realities of the neo-liberal counterrevolution and the ways in which its understanding of ‘freedom’ constitute a danger for a good life of all and the survival of the planet.” —Heinz Sünker, Rudolf Carnap Senior Professor, Bergische Universität Wuppertal, Germany “We are living through a crisis of democracy, during which it is necessary not to go back to Rousseau but to go forward to Rousseau and to explore the ways in which his thought can illuminate our contemporary dilemmas. The interdisciplinary focus and breadth of this stimulating collection will be of great help in this endeavour.” —Andy Kilmister, Senior Lecturer of Economics, Oxford Brookes University, UK This book demonstrates that Rousseau offers a distinctive critical voice which is worthy of listening to. Rousseau is shown to target not merely social ‘injustices’, but the very dynamics central to the ‘form of life’ itself. As such we are able to contemplate, and engage in, a more foundational form of social critique. We contend that by returning to Rousseau, both as a theorist in his own right, and as an interlocutor with the contemporary literature within radical political and social philosophy, we can see both the circumscribed nature of contemporary discussion, and the true importance of Rousseau’s thought. In summary, Rousseau remains a figure of vital importance across disciplines and it is high time for an edited volume which connects insights centring his thought and impact today. Denis Bosseau is a doctoral candidate at the Universityof Sussex, Brighton, UK. Owen Brown is an independent scholar based in Oxford, UK. Neal Harris is a Senior Lecturer in Sociology at Oxford Brookes University, UK. Ployjai Pintobtang is a Lecturer in the department of Government, University of Chiang Mai, Thailand.